Comparative metabolomic and transcriptomic analyses revealed the differential accumulation of secondary metabolites during the ripening process of acerola cherry (Malpighia emarginata) fruit. (14th September 2021) - Xu, Mingfeng; Shen, Chenjia; Zhu, Qin; Xu, Yunsheng; Xue, Changfeng; Zhu, Beiwei; Hu, Jiangning
Abstract: BACKGROUND: Acerola cherry is a famous functional fruit containing plentiful antioxidants and other nutrients. However, studies on the variations among nutrients during the ripening process of acerola fruit are scare. RESULTS: Comparative metabolomic and transcriptomic analyses were performed and identified 31 331 unigenes and 1896 annotated metabolite features in acerola cherry fruit. K Kyoto Encyclopedia of Genes and Genomes enrichment analysis showed that several antioxidant and nutrient‐related metabolic pathways, such as the flavonoids, vitamins, carotenoids, amino acids, and fatty acids metabolic pathways, were significantly changed during the ripening process. The metabolites related to the vitamin, carotenoid, and fatty acid metabolic pathways were downregulated during the ripening process. Several flavonoid biosynthesis‐related genes (including dihydroflavonol 4‐reductase, chalcone synthase, flavanone 3‐hydroxylase, and anthocyanidin synthase), were significantly upregulated, suggesting their essential functions in the accumulation of flavonoids in mature fruit. CONCLUSION: Most of the vitamin and carotenoid metabolism‐related metabolites significantly accumulated in immature fruit, suggesting that immature acerola fruit is a good material for the extraction of vitamins and carotenoids. For macronutrients, most of the amino acids accumulated in mature fruit and most of the fatty acids greatly accumulated in immature fruit. Our data revealed the differential accumulation of antioxidants and nutrients during the ripening process of acerola cherry fruit. © 2021 Society of Chemical Industry.